PENGEMBANGAN MODEL PEMBELAJARAN SIKLUS BELAJAR TERHADAP PENINGKATAN KETRAMPILAN BERPIKIR RASIONAL ANAK SEKOLAH DASAR - Sri Handayani; Sumarno Sumarno (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2016)
The study was conducted to find a suitable model in science learning that can improve rational thinking skills of children. Based on observations in the field of learning science is still centered on the teacher and less provide opportunities for students to build their own knowledge through rational thinking skills. Rational thinking skills need to be developed early on because it is the basis of complex thinking ability to understand the problems of science and mathematics. To achieve these objectives GBPP analysis, teaching materials and learning theories IPA. Furthermore, designing a learning model that fits the model cycle of learning that is based on constructivism views so as to improve rational thinking skills of children. Model of student-centered learning, students' attention to the initial conception and use the student environment as a learning resource. Hallmark of this model is in melaksanakamn learning process in three stages ranging from exploration, introduction of the concept and application of the concept. Data collected mel; Alui achievement test, observation and interviews. Further analysis of data normality, homogeneity and a t test on the test results. Percentage mastery of concepts, rational thinking skills, procedural skills IPA and interviews are described later concluded. The trial results showed that the learning cycle model developed for the adjustment of material living beings meningkatkn rational thinking skills, science process skills and mastery of concepts students.